CONTEXTUAL BASED LEARNING: SEBUAH PENDEKATAN DESKRIPTIF DALAM PENDIDIKAN BAHASA - Astuti, Sri Sakti Wahyu; Sodiq, Syamsul; Indrawati, Dianita; Ahmadi, Anas; Darni (JURNAL SKRIPTA, 2025)
This research aims to describe and formulate an effective Contextual Based Learning (CBL) model in the context of Indonesian language learning. Through the literature study method of various scientific articles, this research analyzes the application of the contextual approach in improving students' language skills, especially in the aspects of writing, reading, and critical thinking. The results of the study show that CBL is able to link learning materials with students' life experiences, social environment, and culture, thus creating more meaningful, participatory, and applicable learning. CBL also demands the active role of teachers as facilitators who are able to design learning based on context and students' real experiences. However, the implementation of CBL faces several challenges such as limited learning resources, teacher training needs, and variations in students' abilities. Therefore, this article recommends the development of a systematic and comprehensive CBL learning model to support the Indonesian language learning process that is more relevant, adaptive, and has a positive impact on students' language skills. Keywords: Contextual Based Learning, Indonesian Language Learning, Language Proficiency